Effects of peroxisomal catalase inhibition on mitochondrial function. - Walton, Paul (Frontiers in Physiology, 2012)
Peroxisomes produce hydrogen peroxide as a metabolic by-product of their many oxidase enzymes, but contain catalase that breaks down hydrogen peroxide in order to maintain the organelle’s oxidative balance. It has been previously demonstrated that, as cells age, catalase is increasingly absent from the peroxisome, and resides instead as an unimported tetrameric molecule in the cell cytosol; an alteration that is coincident with increased cellular hydrogen peroxide levels. As this process begins in middle-passage cells, we sought to determine whether peroxisomal hydrogen peroxide could contribute to the oxidative damage observed in mitochondria in late-passage cells. Early-passage human fibroblasts (Hs27) treated with aminotriazole (3-AT), an irreversible catalase inhibitor, demonstrated decreased catalase activity, increased levels of cellular hydrogen peroxide, protein carbonyls, and peroxisomal numbers. This treatment increased mitochondrial reactive oxygen species levels, and decreased the mitochondrial aconitase activity by ∼85% within 24 h. In addition, mitochondria from 3-AT treated cells show a decrease in inner membrane potential. These results demonstrate that peroxisome-derived oxidative imbalance may rapidly impair mitochondrial function, and considering that peroxisomal oxidative imbalance begins to occur in middle-passage cells, supports the hypothesis that peroxisomal oxidant release occurs upstream of, and contributes to, the mitochondrial damage observed in aging cells.